Comparative evaluation of biofloc and aquamimicry systems : energy fluxes affecting water quality, microbial activity and growth of fish - Lathief, Inamul Hassan Abdul; Salin, Krishna R.; Yakupitiyage, Amararatne; Soni, Peyush; AIT Fellowship (Pathum Thani, Thailand : Asian Institute of Technology, 2017)
The present study comparatively evaluated the water quality dynamics, primary productivity, respiration and fish growth performances with biofloc and aquamimicry systems which used tapioca starch and fermented rice barn as a carbon source. It was carried out in 3500L tanks in triplicates with stoking of 4000 sex-reversed tilapia fry/tank for 8 weeks fed with powdered crumble feed.Results revealed that there was no significant difference in water quality dynamics, primary productivity and respiration between aquamimicry and biofloc systems except nitrate, alkalinity, free CO2and floc volume. In both systems, nitrogen removal was dominated by heterotrophic pathway. But photoautotrophic and chemoautotrophic mediated nitrogen removal were also occurring at a significant level during the initial and towards the end phase respectively. Comparatively, higher rate of chemoautotrophic nitrogen removal was observed in aquamimicry system than biofloc systems.In both systems, the negative NPP and GPP values revealed that systems were predominantly bacterial mediated and functions with serious oxygen deficit requiring continuous aeration. Fish growth performance was not affected by type of culture system. Apart from that, high FCR and the low survival rate were the major concern, can be solved by controlling the total suspended solids and usage of pelleted feed.
A thesissubmittedin partial fulfillment of the requirements for the degree of Master of Science in Aquaculture and Aquatic Resources Management, School of Environment, Resources and Development
Thesis (M.Sc.) - Asian Institute of Technology, 2017
Keywords: Tilapia; Microbial biotechnology; Fishes -- Growth